Board of directors and corporate governance in Nigeria (2013)
The board of directors of a company is a very important organ not only responsible for management but also for adopting good corporate governance and practice in the company. This paper discussed and analyzed with the aid of comparative law, the Code of Corporate Governance in Nigeria and its effect on the board structure, the role, effectiveness and duties of the non-executive directors (NEDs) and how their independence can be assured, guaranteed and monitored to enhance the board’s effectiveness, ensure full compliance with the codes of corporate governance. The regime of compliance and regulation is extremely weak and a case is made for a specialized regulator agency to monitor compliance with the codes, upgrade standard and harmonize the different codes.